2021
DOI: 10.1021/jasms.1c00277
|View full text |Cite
|
Sign up to set email alerts
|

IRMPD Spectroscopy of [PC (4:0/4:0) + M]+ (M = H, Na, K) and Corresponding CID Fragment Ions

Abstract: Glycerophospholipids (GPs) are highly abundant in eukaryotic cells and take part in numerous fundamental physiological processes such as molecular signaling. The GP composition of samples is often analyzed using mass spectrometry (MS), but identification of some structural features, for example, differentiation of stereospecific numbering (sn) isomers by wellestablished tandem MS (MS 2 ) methods, is challenging. In particular, the formation of 1,3-dioxolane over 1,3-dioxane intermediates proposed to be respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…S2 ). In recent studies, MS 2 fragments generated by neutral headgroup loss from protonated [ 13 ], sodiated [ 4 , 10 , 11 ], and potassiated [ 12 ] glycerophospholipids were shown to feature a cyclic dioxolane structure. In order to determine whether silver adduction also yields dioxolane structures and to estimate the respective influence of the headgroup and the lipid chains on the fragment structure, silver-adducted PE and PC precursor ions were subjected to in-source fragmentation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2 ). In recent studies, MS 2 fragments generated by neutral headgroup loss from protonated [ 13 ], sodiated [ 4 , 10 , 11 ], and potassiated [ 12 ] glycerophospholipids were shown to feature a cyclic dioxolane structure. In order to determine whether silver adduction also yields dioxolane structures and to estimate the respective influence of the headgroup and the lipid chains on the fragment structure, silver-adducted PE and PC precursor ions were subjected to in-source fragmentation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neutral headgroup loss in positive ion mode was postulated to proceed via an intramolecular cyclization resulting in a six-membered dioxane ring or five-membered dioxolane ring [ 9 ]. Subsequent studies confirmed the dioxolane structure for alkali metal adducts [ 4 , 10 12 ] and protonated glycerolipid fragments [ 13 ]. Spectroscopic investigations of phospholipid precursor ions explained the formation of dioxolanes by strong interactions between the sn -1 ester and the cation, promoting intramolecular cyclization of the less strongly bound sn -2 ester into a five-membered ring [ 12 ].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…, N-protomer in this case) and are not readily produced directly in the ion source. Although IRPD spectroscopy of fragment ions generated by collision-induced dissociation has been applied to various systems, 42,48,49 we extend herein the methodology to hydrated clusters to reliably determine the protonation site. The cooling efficiency in the QIT is high enough to freeze the conformations of a molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, attachment of Ba 2+ can best stabilized by additional interactions with lipid ester groups, followed by Ca 2+ and Mg 2+ . These interactions between metal cations and lipids play a role in the formation of these complexes has recently been shown for [PC 4:0/4:0 + Na] + by IR multiple photon dissociation spectroscopy …”
Section: Resultsmentioning
confidence: 75%